2014
DOI: 10.1108/s0733-558x20140000042010
|View full text |Cite
|
Sign up to set email alerts
|

Where to Go for a Change: The Impact of Authority Structures in Universities and Public Research Institutes on Changes of Research Practices

Abstract: In this article, we analyse how variations in organisational conditions for research affect researchers' opportunities for changing individual-level or group-level research programmes. We contrast three innovations that were developed in universities and public research institutes in Germany and the Netherlands, which enables comparisons both between organisational settings and between properties of innovations. Comparing the development of three innovations in the two types of organisations enables the identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In planning their projects, researchers anticipate requirements for ERC‐like funding that is oriented towards breakthrough science, thus potentially de‐prioritizing other lines of research that may be equally valuable. As Scholten et al ( 2021 ) stress, this type of excellence funding has strong positive effects on the few researchers and groups that succeed, in the sense that they can build “protected spaces” within the university (Gläser et al, 2014 ). However, these positive effects are counteracted by the negative effects for the many other researchers who do not receive such funding but still neglect more gradual lines of research.…”
Section: Is Breakthrough Research Becoming the New Norm?mentioning
confidence: 99%
“…In planning their projects, researchers anticipate requirements for ERC‐like funding that is oriented towards breakthrough science, thus potentially de‐prioritizing other lines of research that may be equally valuable. As Scholten et al ( 2021 ) stress, this type of excellence funding has strong positive effects on the few researchers and groups that succeed, in the sense that they can build “protected spaces” within the university (Gläser et al, 2014 ). However, these positive effects are counteracted by the negative effects for the many other researchers who do not receive such funding but still neglect more gradual lines of research.…”
Section: Is Breakthrough Research Becoming the New Norm?mentioning
confidence: 99%
“…There is a growing interest in studying the impact of funding and authority changes on research content and practices (Laudel 2006;Hicks and Katz 2011;Hicks 2012;Whitley 2014;Benninghoff et al 2014;Gläser et al 2014;Laudel and Gläser 2014;Gläser and Laudel 2016;Whitley, Gläser, and Laudel 2018;Franssen et al 2018). It is not clear how and to what extent funding policies, with a predictable impact on researchers' decisions as social agents, can also determine the epistemic properties of research.…”
Section: The Policy Of Hypothesis Testingmentioning
confidence: 99%
“…The second lesson we propose to derive from our case study is the following. During the last decades, there has been a growing interest in studying the impact of funding policies on research content and practices (Laudel 2006;Hicks and Katz 2011;Hicks 2012;Whitley 2014;Benninghoff et al 2014;Gläser et al 2014;Laudel and Gläser 2014;Gläser and Laudel 2016;Whitley, Gläser, and Laudel 2018;Franssen et al 2018). For example, it has been observed that changes in funding criteria can induce changes in the experimental or theoretical nature of research (Laudel 2006), but it is not clear what mechanisms are involved and their scope.…”
Section: Introductionmentioning
confidence: 99%
“…These critical junctures include making decisions about changing employers, but are not limited to purely labour market questions. Equally, research careers are shaped by decisions taken on the selection of research topics (Knorr-Cetina 1981), including switching to new topics or discontinuing a research line (Gläser et al 2014). Decisions regarding the opportunity to be geographically mobile (Fernández-Zubieta et al 2015), electing whether to work for a period in international locations or remain within the 'home' context, can also have varying outcomes for scientific performance (Franzoni et al 2014) and career progress (Lawson and Shibayama 2014).…”
Section: Critical Junctures In Research Careersmentioning
confidence: 99%